Atopic dermatitis and non-alcoholic fatty liver disease: current state of evidence and possible pathogenetic correlations - Dębicka, Marta; Bąk, Aleksandra; Walecki, Jerzy; Walecka, Irena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Relationships between inflammatory diseases and metabolic abnormalities are recently raising much scientific interest. Convincing evidence on the association between atopic dermatitis (AD) and constituents of metabolic syndrome (MS) has already been established. In this article we aim to summarize current data on the link between AD and non-alcoholic fatty liver disease (NAFLD), which is considered a hepatic manifestation of MS. By reviewing animal models, human studies and possible pathogenetic points of contiguity we want to present the current state of knowledge and goals for further investigations. To our best knowledge, this is the first review of this topic so far.